1999
DOI: 10.1007/bf03182546
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of aerodynamic effects on a double-delta wing aircraft model using Pressure Sensitive Paint (PSP) technique

Abstract: Visualization of aerodynamic effects on a three-dimensional double-delta wing aircraft model was conducted using an optical pressure measurement system, based on the Pressure Sensitive Paint (PSP) technique, and in addition a laser-light sheet method. The combination of PSP technology with the laser-light sheet method, provides a good understanding of the flow around the wind tunnel model. In recent years, this novel PSP-technology has attracted considerable attention in the aerospace community. The PSP techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…From the literature it has been found that typically the uncertainty of an intensity method PSP system is 15mbar and that of the lifetime being 5mbar. With temperature compensation these may be improved to 5mbar and 1⋅5mbar respectively (10,11) .…”
Section: Use Of Luminescent Paintmentioning
confidence: 99%
“…From the literature it has been found that typically the uncertainty of an intensity method PSP system is 15mbar and that of the lifetime being 5mbar. With temperature compensation these may be improved to 5mbar and 1⋅5mbar respectively (10,11) .…”
Section: Use Of Luminescent Paintmentioning
confidence: 99%